True Anemia─Red Blood Cell Volume Deficit─in Heart Failure: A Systematic Review. (May 2017) - Montero, David; Lundby, Carsten; Ruschitzka, Frank; Flammer, Andreas J.
Abstract : Background—: Anemia in heart failure (HF) is commonly diagnosed according to hemoglobin concentration [Hb], hence may be the result of hemodilution or true red blood cell volume (RBCV) deficit. Whether true (nonhemodilutional) anemia in HF can or cannot be generally inferred by [Hb] measurements and clinical correlates remains unclear. The purpose of this study was to systematically review the literature and investigate the status and correlates of RBCV in patients with HF. Methods and Results—: MEDLINE, Scopus, and Web of Science were searched since their inceptions until April 2016 for articles directly reporting or allowing the calculation of intravascular volumes (RBCV, plasma volume) in patients with HF according to the International Council for Standardization in Hematology. Eighteen studies were included after systematic review, comprising a total of 368 patients with HF (limits for mean age=49–80 years, sex=0%–92% females, left ventricular ejection fraction=26%–61%). Mean RBCV was reduced (limits=67%–88% of normal) in all studies including HF patients with anemia (low [Hb]) (7 studies, n=127), whereas only 2 of 10 studies in nonanemic patients with HF presented lower than normal mean RBCV (90% and 96%). In metaregression analyses, RBCV was positively associated with [Hb] ( B =6.10, SE=1.44) and negatively associated with age ( B =−1.14, SE=0.23), % females ( B =−0.38, SE=0.04), left ventricular ejection fraction ( B =−0.81, SE=0.20), and body mass index ( B =−3.55, SE=0.46; P <0.001). Conclusions—: Presence or absence of true anemia in patients with HF as determined by RBCV status mainly concurs with diagnosis based on [Hb] and presents negative relationships with age, female sex, left ventricular ejection fraction, and body mass index. Abstract : Supplemental Digital Content is available in the text.